The Leadership Gap: What Gets Between You and Your Greatness - Stacey F. Stearns (Journal of Applied Communications, 2018)
A review of The Leadership Gap: What Gets Between You and Your Greatness, by Lolly Daskal.
Keywords: leadership; professional development; personal growth